Dynamic sliding mode control of single‐stage boost inverter with parametric uncertainties and delay. Issue 12 (24th March 2021) - Mohammadhassani, Farideh; Narm, Hossein Gholizade
Abstract: Here, a novel control strategy based on sliding mode control for the single‐stage boost inverter is presented. The goal is to achieve a system with robustness against inherent delays and variations in parameters, fast response, and high‐quality AC voltage. Therefore, according to the idea of current‐mode control, a new type of dynamic sliding mode control (DSMC) is proposed to improve the response performance on various input and parameter operation conditions. In comparison with the conventional controllers, the proposed DSMC utilized only a single loop while presenting attractive features such as robustness against parametric uncertainties and input delay by definition new sliding surfaces. Furthermore, the proposed system has a fast and chattering‐free response, provides an appropriate steady‐state error, good total harmonic distortion (THD), while its implementation is very simple. In a fair comparison with conventional sliding mode control, simulations and laboratory experiments verified satisfactory performance and effectiveness of the DSMC method.